Pengaruh Promosi Digital, Kepercayaan Konsumen, Dan Pengalaman Pelanggan Terhadap Volume Penjualan Pada Dapur Gendis Madiun - Dina Nur Halisa; Mintarti Indartini; Hartirini Warnaningtyas (Universitas Merdeka Madiun, 2025)
The objectives of this study are (1) to partially analyze the influence of digital promotion, consumer trust, and customer experience on sales volume at Dapur Gendis Madiun. (2) simultaneously analyze the influence of digital promotion, consumer trust and customer experience on sales volume at Dapur Gendis Madiun.. The population in this study is female consumers in the Gendis Kitchen aged 15-18 years. The sample from this study is 96 samples, with 60 samples coming from filling out questionnaires online, and 36 filling out questionnaires in person. The type of research used is associative quantitative, with data collection techniques through questionnaires and interviews. The results of the research show that (1) partially affect digital promotion, consumer trust, and customer experience affect the sales volume at Dapur Gendis Madiun. (2) simultaneously affect digital promotion, consumer trust, and customer experience on sales volume at Dapur Gendis Madiun. (3) Customer experience proved to be the most dominant factor in influencing sales volume at Dapur Gendis Madiun.